Qualitative and quantitative analysis of buffalo ovaries, follicles and oocytes in view of in vitro production of embryos (Bangladesh Journal of Animal Science, 2012)
This study was conducted to evaluate the buffalo ovaries, follicles and cumulus-oocyte-complexes (COCs) with the view of in vitro production (IVP) of embryos. Buffalo (Bubalis bubalis) ovaries were collected from local slaughterhouse and categorized according to the position of ovaries in the genital tract (left vs. right) and presence or absence of corpus luteum (CL). Moreover, collected ovaries were also evaluated for length, width and weight, number of follicles, aspirated follicles and state of COCs. The length (cm) of right ovary (2.32±0.06) was significantly (P